Profil of Students’ Mathematical Literacy in Solving AKM Task in Terms of Personality Types - Cecylia May Cahyani; Susanah Susanah (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2022)
Mathematical literacy is an individual’s ability to formulate, employ, and interpret mathematics in various contexts. AKM is one of the government's efforts to measure students' mathematical literacy. This research is a descriptive research with a qualitative approach that aims to describe the profile of students' mathematical literacy in solving AKM in terms of the melancholic, choleric, phlegmatic, and sanguine personality types. The instrument used are personality type questionnaire, mathematical literacy test, and interview guidelines. The results showed that (1) melancholic students wrote complete information, construct mathematical models, used efficient and structured strategies, performed calculations correctly, interpreted and double-checked answers as a whole; (2) choleric students wrote complete information, did not make mathematical models, used structured strategies, performed calculations correctly, interpreted and re-checked answers, but were less careful so the units used were not appropriate; (3) phlegmatic students wrote complete information, construct mathematical models, used quick strategies, interpreted and re-checked calculations, but were less careful so the calculations were not accurate; (4) Sanguine students did not write down known information, did not make mathematical models, used quick strategies, interpreted solutions, but did not re-check answers so the calculations were inaccurate. Therefore, personality type is one of the factors that cause differences in mathematical literacy. Keywords : mathematical literacy, akm, personality type.